2020
DOI: 10.3390/s20185252
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Systems Security Approach Featuring Thin Secure Elements for Resilient IoT Deployments

Abstract: IoT systems differ from traditional Internet systems in that they are different in scale, footprint, power requirements, cost and security concerns that are often overlooked. IoT systems inherently present different fail-safe capabilities than traditional computing environments while their threat landscapes constantly evolve. Further, IoT devices have limited collective security measures in place. Therefore, there is a need for different approaches in threat assessments to incorporate the interdependencies bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This is an acronym for damage, reproducibility, exploitability, affect users, and discoverability [ 65 , 66 ], which are the categorizations used to quantify risk in this methodology. Furthermore, such a methodology can be viewed as a way of measuring the vulnerability risk associated with each associated threat [ 67 ] through the use of numerical values. Additionally, it is observed that each of the five categories is evaluated from 0 to 3, where zero is the absence of risk and three is the highest value (a more detailed quantification can be seen in the Table 4 ) since using this table helps reduce the subjectivity inherent to DREAD, which has been considered a drawback of this method.…”
Section: Methodsmentioning
confidence: 99%
“…This is an acronym for damage, reproducibility, exploitability, affect users, and discoverability [ 65 , 66 ], which are the categorizations used to quantify risk in this methodology. Furthermore, such a methodology can be viewed as a way of measuring the vulnerability risk associated with each associated threat [ 67 ] through the use of numerical values. Additionally, it is observed that each of the five categories is evaluated from 0 to 3, where zero is the absence of risk and three is the highest value (a more detailed quantification can be seen in the Table 4 ) since using this table helps reduce the subjectivity inherent to DREAD, which has been considered a drawback of this method.…”
Section: Methodsmentioning
confidence: 99%
“…On one hand, lightweight, low-power security algorithms were proposed [ 25 ]. On the other hand, there is a novel practice to design devices with built-in secure elements [ 26 ], following the hardware-based security approach [ 27 ]. Another manufacturing-based solution to protect against physical cloning implies the use of physical, unclonable functions [ 22 , 28 ] that assigns the device a unique fingerprint.…”
Section: Security In the Internet Of Thingsmentioning
confidence: 99%
“…By analyzing information from physical side-channels such as power consumption, timing or electromagnetic emissions, even mathematically secure cryptographic algorithms can be effectively compromised. The relevance and necessity of hardware device protection [10] are further underscored by standards that define required levels of physical protection for specific classes and types of devices. Some notable standards that encompass hardware protection include Common Criteria, TEMPEST, FIPS, IEEE and IEC CISPR, to name a few.…”
Section: Introductionmentioning
confidence: 99%